A Qualitative Exploration of Occupational Adaptation in Caregivers of People with Multiple Sclerosis. Issue 1 (2nd January 2021) - Motaharinezhad, Fatemeh; Hassani Mehraban, Afsoon; Lajevardi, Laleh; Ghahari, Setareh; Salimi, Yahya
Abstract: Due to the unpredictable and progressive nature of multiple sclerosis, the burden of care is placed on the primary caregivers. This study aimed to explore occupational adaptation strategies implemented by primary caregivers to adapt to occupational challenges of caregiving. Seventeen primary caregivers of people with MS were interviewed using purposive sampling techniques. Data were analyzed using content analysis method. Two main categories of strategies were determined: (a) Strategies to alleviate intrapersonal challenges of occupational adaptation; and (b) Strategies to alleviate environmental challenges of occupational adaptation. These included various skills and solutions that aided primary caregivers' adaptation toward occupational challenges. Based on the results of this study, occupational adaptation is a means of achieving mastery in alleviating occupational challenges to cope with adverse circumstances. The results of this study can be used to help therapists design appropriate caregiver-focused interventions, ultimately improving caregiver performance.